O que a criança tem a dizer sobre o que se nomeia como dificuldades de aprendizagem - Maria Alice Moreira Lima (2015)
This research aims to demonstrate that the silencers and secreting effects of the socially established knowledge, about the difficulties of learning, even though present, do not prevent that children find ways to show, in its singularity, as capable of producing a knowledge about what happens to them at school. Therefore, begins by examining the two best-known child psychiatry manuals, produced throughout the twentieth century, Kanner (1935) and Ajuriaguerra (1970), in order to identify the ways in which deadlocks children with school education are named originally. Psychiatric science, as we know, was the first to welcome this unwanted product of the process who establishes the education as mandatory in the occident: learning difficulties. Later, undertakes the identification of how the phenomenon of learning disabilities is circumscribed in the teachers speech in the municipal education in Belo Horizonte. It was found there a reproduction of a way of understanding what is happening with children in school, that dating back to the fundamentals of the process of 'renewal' pedagogical, known as New School. From this perspective, the learning difficulties are conceived in the context of a range of variables that intrudes in the learning process designed as an adaptive effort of individuals, in accordance with environmental variables. Finally, this research, listens to children identified as having difficulties to learn, about this supposed difficulty. The same surprise to show that they are not at all silenced by knowledge imposed to them, proving yourselfers able to say about what happens to them in school and how they create survival strategies for its singularity among many generalizing knowledge. The work undertaken has, in psychoanalytic theory, especially in the Lacanian orientation, its main references. The target permitted by psychoanalysis, was what make possible to challenge the established knowledge and, on the other hand, opening the possibility of speech to children. The ethical psychoanalysis, referenced in the incompleteness of all knowledge and in the insistence that the subject produces the know about what happens to him, became thus, the guiding methodological orientation of research.